Facets of the North Korea conflict: Actors, problems and Europe's interests - Hanns Günther Hilpert; Oliver Meier (Stiftung Wissenschaft und Politik (SWP), 2018)
Even after the summit meeting between US President Donald Trump and North Korea's Head of State Kim Jong Un in Singapore on 12 June 2018, the crisis surrounding North Korea's nuclear programme and weapons of mass destruction programme remains one of the most dangerous and complex in the world. The conflict is centred on the unresolved tense relationship between North Korea and the USA, and in particular the issue of nuclear weapons possession. Grouped around this are other conflicts characterised by clashes of interests between China, Japan, North Korea, Russia, South Korea and the USA. In addition, within these conflicts, security policy, human rights policy and economic policy have great impact on each other. For Germany and Europe, finding a peaceful solution to the conflict - or at least preventing military escalation - is key. Europe can and should work to ensure that North Korea is treated as a challenge to global governance. Addressing the set of problems subsumed under the term "North Korea conflict" in such a way as to avoid war, consolidate global order structures, and improve the situation of the people in North Korea requires staying power and can only lead to success one step at a time.
Keywords: 320